2003
DOI: 10.1074/jbc.m212353200
|View full text |Cite
|
Sign up to set email alerts
|

An NMR-based Model of the Ubiquitin-bound Human Ubiquitin Conjugation Complex Mms2·Ubc13

Abstract: A heterodimer composed of the catalytically active ubiquitin-conjugating enzyme hUbc13 and its catalytically inactive paralogue, hMms2, forms the catalytic core for the synthesis of an alternative type of multiubiquitin chain where ubiquitin molecules are tandemly linked to one another through a Lys-63 isopeptide bond. This type of linkage, as opposed to the more typical Lys-48-linked chains, serves as a non-proteolytic marker of protein targets involved in error-free postreplicative DNA repair and NF-B signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
121
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(135 citation statements)
references
References 49 publications
12
121
0
2
Order By: Relevance
“…While not clearly shown for E2-25K, other work shows the UBA affinity for ubiquitin increases as the chain length increases (66,67). This mechanism bears a strong analogy to that recently uncovered for the Mms2/Ubc13 heterodimer involved in Lys 63 polyubiquitin chain formation (12)(13)(14). In this complex a thiol ester is formed between the canonical E2 Ubc13 and ubiquitin.…”
Section: The C Terminus Of Ubc1mentioning
confidence: 89%
See 1 more Smart Citation
“…While not clearly shown for E2-25K, other work shows the UBA affinity for ubiquitin increases as the chain length increases (66,67). This mechanism bears a strong analogy to that recently uncovered for the Mms2/Ubc13 heterodimer involved in Lys 63 polyubiquitin chain formation (12)(13)(14). In this complex a thiol ester is formed between the canonical E2 Ubc13 and ubiquitin.…”
Section: The C Terminus Of Ubc1mentioning
confidence: 89%
“…While these structures show the interactions between the E2, E3, and ubiquitin proteins, details how the transfer of ubiquitin to the substrate occurs and how the polyubiquitin chain is constructed are more uncertain. More recently, three-dimensional structures of the heterodimeric complex between the canonical E2 protein Ubc13 in complex with an E2 variant protein Mms2 have shown how these proteins function together to assemble Lys 63 -linked polyubiquitin chains (12)(13)(14). Similar structural details for construction of Lys 48 -linked polyubiquitin chains are not available, although it has been suggested that dimeric forms of other E2 proteins might also be required (15,16).…”
mentioning
confidence: 99%
“…With the yeast homolog of UbcH13/Uev1a, Ubc13/Mms2, this formation of Lys 63 linkages has been shown to be due to the noncovalent binding on Mms2 of the preceding Ub so as to transfer the Ub from the E2 specifically to Lys 63 (49,50). In this case, as in SCF working with Cdc34 (51), the E3 appears to accelerate on the substrate the same process of chain synthesis, which the E2 can slowly catalyze by itself.…”
Section: Formation Of Homogeneous or Heterogeneous Forked Ubmentioning
confidence: 99%
“…Accordingly, seven different topologies of polyubiquitin can be generated (excluding mixed topologies) (18). Although most ubiquitin-dependent proteasomal degradations were found to be mediated by Lys 48 polyubiquitin chains, certain evidence suggests that Lys 6 (19), Lys 11 (19,20), and Lys 29 (21) may also target substrates for proteasomal degradation. Polyubiquitinations through nonLys 48 lysines exist in vivo and play a role in a range of cellular processes (22,23).…”
mentioning
confidence: 99%
“…Because ubiquitin harbors seven lysine residues (Lys 6 , Lys 11 , Lys 27 , Lys 29 , Lys 33 , Lys 48 , and Lys 63 ), in principle, chains of polyubiquitin can be formed via a bond between the C-terminal glycine of one ubiquitin molecule and an ⑀-amine of any of the seven lysine residues of another ubiquitin. Accordingly, seven different topologies of polyubiquitin can be generated (excluding mixed topologies) (18).…”
mentioning
confidence: 99%